Zeke Meeks vs. the putrid Puppet Pals - Green, D. L. (Debra L.) (Zeke Meeks, 2012)
All the children in the third grade except Zeke Meeks are playing with the newest fad, Puppet Pals finger puppets--will Zeke give in to the pressure and join them, even though he would much rather play basketball?